"I'm a Teacher, I'm Gonna Always Protect You": Understanding Black Educators' Protection of Black Children. (February 2021) - McKinney de Royston, Maxine; Madkins, Tia C.; Givens, Jarvis R.; Nasir, Na'ilah Suad
Many Black educators in the United States demonstrate a political clarity about white supremacy and the racialized harm it cultivates in and out of schools. We highlight the perspectives of some of these educators and ask, (1) How do they articulate the need to protect Black children? and (2) What mechanisms of protection do they enact in their classrooms and schools? Through further elaborating the politicized caring framework, our analyses show how Black educators disrupt the racialized harm produced within schools to instead (re)position Black students as children worthy of protection via caring relationships, alternative discipline policies, and other interpersonal and institutional mechanisms. This study has implications for teaching, teacher education, and how the "work" of teachers is conceptualized and researched.